2008
DOI: 10.1159/000118033
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Venous Outflow after Right Hepatic Living Donor Liver Transplantation with a Venous Graft Patch

Abstract: Between March 2002 and September 2004, 36 patients at Mie University Hospital underwent living donor liver transplantation (LDLT) of a right lobe graft without the middle hepatic vein. The patients were divided into two groups: group I (n = 25) received ordinary hepatic vein anastomoses, and group II (n = 11) received a venous graft patch in the subsequent procedure. Between groups, we compared hepatic vein blood flow (ultrasound), liver volume (CT scan), laboratory data, and ascitic fluid volume. Outflow bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that ligation of large MHV tributaries could bring about more remarkable perfusion imbalance between anterior and posterior segments [42]. As a result, the vascular diameter of the MHV tributaries is the mostly recommended criteria for reconstruction and 5 mm is commonly preferred as a demarcation [13,14,16,17,18,19,20,21,23,25,26,28,29,30,32,35], while others have suggested that MHV reconstruction should be based on the clamping test findings [13,17,21,26,29,32,35], graft volume [21,23,43] and the number of the MHV tributaries [23,24,31,33]. The policy of our center for MHV tributaries reconstruction had been described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that ligation of large MHV tributaries could bring about more remarkable perfusion imbalance between anterior and posterior segments [42]. As a result, the vascular diameter of the MHV tributaries is the mostly recommended criteria for reconstruction and 5 mm is commonly preferred as a demarcation [13,14,16,17,18,19,20,21,23,25,26,28,29,30,32,35], while others have suggested that MHV reconstruction should be based on the clamping test findings [13,17,21,26,29,32,35], graft volume [21,23,43] and the number of the MHV tributaries [23,24,31,33]. The policy of our center for MHV tributaries reconstruction had been described above.…”
Section: Discussionmentioning
confidence: 99%
“…For a modified right lobe there would be technical difficulty as to the additional reconstruction of the MHV tributaries. Firstly, the source of optimal venous grafts for the procedure remains a concern, whether it is cryopreserved or autologous or prosthetic vein grafts [3,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Secondly, an appropriate reconstruction policy also remains a concern, which could obviate additional procedures and possible outflow problems.…”
Section: Introductionmentioning
confidence: 99%
“…In LDLT using a right lobe graft, the use of a venous graft patch has been effective in maximizing venous outflow. 24 This technique involves an end-to-side anastomosis and the use of a venous graft patch attached only to the anterior side of the anastomosis; this might be a feasible procedure for left-sided lobe grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Outflow is affected by the construction of the hepatic vein. 5,6 Intrahepatic vascular resistance is related to the size and quality of the graft. 7,8 Hemodynamic status is related to the development of collateral vessels and spleen volume.…”
mentioning
confidence: 99%